The Role of Customer Trust in Mediating the Influence of Service Quality on Customer Loyalty of Express Laundry Members Palangka Raya - Rita Yuanita Toendan; Noorjaya Nahan (Jurnal Pengabdian Pancasila (JPP), 2023)
This research in the field of marketing management aims to determine the effect of service quality and customer trust on customer loyalty of Express Laundry members in Palangka Raya. Customer trust is a good relationship with management as a business strategy to achieve customer loyalty. While customer quality is a business measure that will be assessed by customers to be loyal and have an impact on business profits. The type of research used is explanatory research, which is to examine the relationship between variables which is the basis for improving purchasing decisions. Research respondents totaled 102 members of Express Laundry. Tested with non-probability sampling technique through the PLS statistical program. The results showed that customer trust and service quality affect the customer loyalty of members of Express Laundry Palangka Raya. The limitations of research on members, become a reference for further research in taking samples of new customers on purchase intentions.